An in Silico approach to multi-epitope subunit vaccine development against SARS COV-2 using Membrane Glycoprotein - Rafsan, Rian (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.